FBSA: A Self-adjustable Multi-source Data Scheduling Algorithm for P2P Media Streaming - Chen, Shuangjia; Huo, Longshe; Fu, Qiang; Guo, Rui; Gao, Wen (Multimedia Content Analysis and Mining, 2007)
Recently, there is great interest of using P2P network in multi-source media streaming. In this paper, we present a self-adjustable scheduling algorithm for multi-source P2P media streaming, called feedback based scheduling algorithm (FBSA). FBSA is simple to implement, fully distributed, asynchronous, and can afford better quality of service. Furthermore, it can adjust itself automatically to adapt network heterogeneity, load variety, bandwidth fluctuation, and overlay dynamics. We have implemented FBSA, and tested it in a P2P live media streaming system: AVStreamer. Experimental results show that FBSA outperforms other conventional P2P data scheduling algorithms, especially in heterogeneous networks.